O USO DE PROCESSOS ELETROQUÍMICOS DE OXIDAÇÃO AVANÇADA NA DEGRADAÇÃO DA FENACETINA E SUA APLICAÇÃO COMO RECURSO METODOLÓGICO ENVOLVENDO O ENSINO DE QUÍMICA - RICARDO CARDOSO (2023)
ABSTRACT The pollution of water sources due to the bioaccumulation of persistent contaminants is becoming increasingly serious, and conventional treatment methods are not effective in removing these pollutants. Therefore, the main objetive of this study is to investigate the use of electrochemical advanced oxidation processes (EAOPs) through a central composite design (CCD) based on response surface methodology (RSM) to plan and optimize the treatment parameters for the removal of phenacetin (PNT), a drug mainly used as ao analgesic, using three processes: electro-Fenton (EF), anodic oxidation with hydrogen peroxide (AO-H2O2), and solar photo electro-Fenton (PEFS). The EF and OA-H2O2 processes were performed in a 100 mL reactor, while the PEFS was carried out in an 8.0 L solar photoreactor, coupled to an electrochemical cell. Boron-doped diamond (BDD) or Pt electrodes were used as the anode and a carbon-PTFE mesh as the cathode. Through experimental planning, the linear, quadratic, and interaction effects of the variables, as well as the optimum operating conditions, were obtained using Minitab Statistical software. According to the data obtained from the analysis of variance, regression coefficients (R2), and diagnostic plots, the model shows a good correlation between the observed and predicted values. Thus, the EF/BDD process, under optimal operating conditions (i.e. [PNT] = 25 mg L-1, [Fe2+] = 32.7 mg L-1, j = 84.7 mA cm-2 and 14 min for degradation and 230 min for mineralization), achieved 81.7% and 78.2% degradation and mineralization of PNT, respectively, in ultrapure water and 63.2% degradation of PNT and 66.5% mineralization of organic matter in secondary effluent. In the EF/Pt process, under ideal conditions ([PNT] = 25 mg L-1, [Fe2+] = 25.3 mg L-1, j = 59.5 mA cm-2 and 14 min and 230 min for degradation and mineralization, respectively), there was 83.9% and 45.2% degradation and mineralization of PNT, respectively, in ultrapure water, and 68.4% degradation and 39.4% mineralization in the effluent. The AO-H2O2 process carried out in effluent and under optimal conditions (pH = 7.05, j = 102 mA cm-2 and 13 min for degradation and 214 min for mineralization), achieved 65.6% degradation and 51.9% mineralization. In the PEFS process, carried out in effluent and under ideal operating conditions ([Fe2+] = 16.8 mg L-1, j = 45.9 mA cm-2 and 36 min for degradation and 181 min for mineralization), 55.9% and 37.1% degradation and mineralization were observed, respectively, with an energy consumption of only 0.14 kWh g-1. The toxicity of the treated solutions was evaluated using two different organisms. In Artemia salina, the EF and AO-H2O2 processes eliminated the toxicity of the solutions, while the PEFS process significantly reduced toxicity. In Lactuca sativa, only the EF process showed no acute toxicity, while the AO-H2O2 and PEFS processes showed a slight inhibition of seed germination. Finally, three degradation routes were presented, with the identification of 12 intermediates. Additionally, the use of EAOPs as an experimental device was proposed to apply an active team-based methodological approach to teaching chemistry to elementary school students making chemistry classes more engaging, didactic, and challenging. Many students rate team-based learning (TBL) positively because they find it interesting and attractive, especially when working in teams. Keywords: Advanced oxidative electrochemical processes, ecotoxicity, experimental design, team-based learning.